Mass Spectrometry-based in vitro Assay to Identify Drugs that Influence Cystine Solubility - Bose, Neelanjan (Bio-Protocol, 2017)

(untitled) (Bio Protoc)
Cystinuria is a rare genetic disorder characterized by recurrent, painful kidney stones, primarily composed of cystine, the dimer of the amino acid cysteine (Sumorok and Goldfarb, 2013). Using a mouse model of cystinuria, we have recently shown that administration of drugs that increase cystine solubility in the urine can be a novel therapeutic strategy for the clinical management of the disease ( Zee et al., 2017 ). There is a large unmet need in the field for developing new drugs for cystinuria. To that end, here we describe a simple in vitro cystine solubility assay that is amenable for screening compounds to identify potential drugs that may influence cystine solubility. The assay includes preparing a supersaturated solution of cystine, incubating this solution with drug(s) of choice, and finally using high pressure liquid chromatography–tandem mass spectrometry (HPLC-MS/MS) to quantify the amount of cystine precipitated under various conditions.